Adorno and Democracy : The American Years - Mariotti, Shannon L. (Shannon Lee) (Book collections on Project MUSE., 2016)
In Adorno and Democracy, Shannon L. Mariotti explores how philosopher Theodor Adorno's fifteen years in the United States prompted a concern for and commitment to democracy that shaped the rest of his oeuvre. She analyzes the extensive and undervalued works Adorno composed in English for an American audience and traces the development of his political theory during the World War II era. Her unique study examines how Adorno changed his writing style while in the United States in order to directly address the public, which lay at the heart of his theoretical concerns. Despite his apparent contempt for popular culture, his work during this period clearly engages with a broader public in ways that reflect his deep desire to understand the problems and possibilities of democracy as enacted through the customs and habits of American citizens. Mariotti incisively demonstrates how Adorno's unconventional and challenging interpretations of U.S. culture can add conceptual rigor to political theory and remind Americans of the normative promise of democracy. Adorno and Democracy is an innovative contribution to critical debates about contemporary U.S. politics. -- from back cover.